Metafora Dalam Lirik Lagu Album Berhati Karya Sal Priadi - Zikri Alfiya; Indra Perdana; Lazarus Linarto; Albertus Purwaka; Misnawati Misnawati (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2023)
The purpose of this research is to describe (1) the types of metaphors found in the lyrics of the album "Berhati" by Sal Priadi, and (2) the functions of metaphors in the lyrics of the album "Berhati" by Sal Priadi. This research is a qualitative descriptive study. The data source for this research is the lyrics of the album "Berhati" by Sal Priadi, which consists of the songs titled "Nyala," "1-2-Cha-Cha," "Malam-Malam Ubud," "Di Timur," "Melebur Semesta," "Kultusan," "Ikat Aku di Tulang Belikatmu," "Amin Paling Serius," "Dalam Diam," and "Jelita." The data in this study are the types and functions of metaphors found in the lyrics of the album "Berhati" by Sal Priadi, in the form of words, phrases, clauses, and sentences that are present in the lines and stanzas of the lyrics related to the types and functions of metaphors. The data collection technique used in this research is literature review, observation, note-taking, and data cards. The data analysis is done using qualitative content analysis. Based on the analysis results, it can be concluded that there are types and functions of metaphors used by the songwriter in the lyrics of the album "Berhati" by Sal Priadi. The types of metaphors found in the lyrics of the album "Berhati" by Sal Priadi include anthropomorphic metaphors, synesthetic metaphors, abstract metaphors, and bestial metaphors. The functions of metaphors found in the lyrics of the album "Berhati" by Sal Priadi include informational function, expressive function, directive function, and phatic function. The most abundant data are found in the category of abstract metaphors and informational function of metaphors, while the least amount of data are found in the category of bestial metaphors and expressive function of metaphors.